Low-dose capecitabine (Xeloda) for treatment for gastrointestinal cancer - Miger, Jasmine (Springer US, 2014)
The prodrug capecitabine (Xeloda) has been an important drug for treatment for gastrointestinal cancer (GI-cancer). This study explores the efficacy of continuous metronomic Xeloda, as well as tolerability and best response during treatment. Patients (n = 35) with stage IV GI-cancer were included in the study and were divided into two groups; upper (n = 13) and lower (n = 22) GI-cancer. All patients were given continuous metronomic Xeloda (500 mg × 2). Best response was measured by radiological and clinical examination including laboratory results. Standard RECIST criteria were used. Median age was 66 (range 29–86). Those patients who received first and second line had the longest duration of treatment. For patients with metastatic gastrointestinal cancer, metronomic capecitabine (Xeloda) may be beneficial both as far as tumor control and quality of life is concerned. In this pilot study, palliation for more than 2 years is observed for 6 of the 35 patients.